The Xanthomonas campestris pv. vesicatoria Type-3 Effector XopB Inhibits Plant Defence Responses by Interfering with ROS Production. - Priller, Johannes; Reid, Stephen; Konein, Patrick; Dietrich, Petra; Sonnewald, Sophia (PLoS ONE, 2016)
The bacterial pathogen Xanthomonas campestris pv. vesicatoria 85-10 (Xcv) translocates about 30 type-3 effector proteins (T3Es) into pepper plants (Capsicum annuum) to suppress plant immune responses. Among them is XopB which interferes with PTI, ETI and sugar-mediated defence responses, but the underlying molecular mechanisms and direct targets are unknown so far. Here, we examined the XopB-mediated suppression of plant defence responses in more detail. Infection of susceptible pepper plants with Xcv lacking xopB resulted in delayed symptom development compared to Xcv wild type infection concomitant with an increased formation of salicylic acid (SA) and expression of pathogenesis-related (PR) genes. Expression of xopB in Arabidopsis thaliana promoted the growth of the virulent Pseudomonas syringae pv. tomato (Pst) DC3000 strain. This was paralleled by a decreased SA-pool and a lower induction of SA-dependent PR gene expression. The expression pattern of early flg22-responsive marker genes indicated that MAPK signalling was not altered in the presence of XopB. However, XopB inhibited the flg22-triggered burst of reactive oxygen species (ROS). Consequently, the transcript accumulation of AtOXI1, a ROS-dependent marker gene, was reduced in xopB-expressing Arabidopsis plants as well as callose deposition. The lower ROS production correlated with a low level of basal and flg22-triggered expression of apoplastic peroxidases and the NADPH oxidase RBOHD. Conversely, deletion of xopB in Xcv caused a higher production of ROS in leaves of susceptible pepper plants. Together our results demonstrate that XopB modulates ROS responses and might thereby compromise plant defence.